Nilai-Nilai Budaya Sumpah Sopi (Rbui Tuk) Perkawinanadat Masyarakat Watmuri Kecamatan Nirunmas - Nifmaskossu, Regina; Feninlambir, Moses; Elisa, Devi (Jurnal Ilmiah Wahana Pendidikan, 2023)
The people of Watmuri village have diverse cultural backgrounds, one of which is the sopi oath culture (Rbui Tuk). The oath of sopi is obligatory for everyone who, and when in marriage the spouses do according to what is sworn, then in their domestic life they must get married even though they are not married or some are married. The purpose of the study of cultural values in the Sopi Oath (Rbui Tuk) here is to describe the cultural values in the Sopi Oath (Rbui Tuk) in traditional marriages of the Watmuri village community, Nirunmas District, Tanimbar Islands Regency as follows. (1) Cultural valuesin human relations as individuals have the value of togetherness in making decisions and the value of loyalty, (2) Cultural values in relations with society, (3) Cultural values in human relations with God have the value of uniting humans with God. The method used is descriptive qualitative